A Study on the Commercialization Path and Sustainable Development of Intangible Cultural Heritage: A Case Study of Digital Platforms - 陶丽; 李文骥 (Journal of Frontier in Economic and Management Research, 2026)
As a vital carrier of human cultural diversity, intangible cultural heritage (ICH) faces significant challenges regarding its preservation and inheritance in contemporary society. Against the backdrop of a rapidly evolving digital economy, leveraging digital platforms to promote the market-oriented operation of ICH has emerged as a crucial pathway for achieving its living transmission and sustainable development. Grounded in cultural capital theory, sustainable development theory, and platform economy theory, this paper systematically analyzes the specific pathways through which ICH can achieve commercialization via digital platforms. These pathways primarily manifest in three core operational models: transaction platform models, customized service models, and video-based teaching models. The study finds that digital platforms can effectively expand the market reach of ICH products, stimulate consumer demand, and reshape the ecosystem of inheritance. However, this process also confronts profound challenges, including the dilution of cultural authenticity, tendencies towards excessive commercialization, the exacerbation of inequality in inheritance due to the digital divide, and the lack of robust intellectual property protection. This paper argues that the commercialization of ICH and its cultural preservation are not inherently contradictory. The key lies in establishing a tripartite framework for sustainable development, guided by "cultural value leadership, market mechanism drive, and institutional system safeguards." Accordingly, the paper proposes several policy recommendations, such as establishing an assessment mechanism for cultural authenticity, improving the governance system of digital platforms, fostering multi-stakeholder collaboration, and advancing innovations in the intellectual property system for ICH. These recommendations aim to provide theoretical references and practical guidance for the preservation, transmission, and development of ICH in the digital era.